Community Empowerment Through the Village-Owned Enterprise "Bareng Lestari" in Bareng Village, Sawahan Subdistrict, Nganjuk Regency - Ika Shania Cahyaning Atie; Agus Widyarta (ARISTO, 2024)
This research aims to analyze community empowerment through the Village-Owned Enterprise "Bareng Lestari" in Bareng Village, Sawahan Subdistrict, Nganjuk Regency. The type of this research is qualitative-descriptive research with data collection techniques in the form of observation, interviews, and documentation. The theory applied in this study is the 5P community empowerment approach, namely enabling, strengthening, protecting, supporting, and maintaining. The results of this research indicate that the community becomes empowered after the establishment of the village-owned enterprise (BUMDES) "Bareng Lestari", yet, this has not been achieved maximally. Out of the 5 indicators, 3 of them have been successfully achieved, including Strengthening, carried out by amplifying the BUMDES internally and externally by providing socialization and counseling for the community in Bareng Village; Supporting, can be seen from the existence of strong partnership networks, marketing of local products and processed products, as well as subsidized fertilizers;and Maintaining, carried out in all aspects including physical maintenance and the maintenance carried out in all fields starting from quality, existence, business units and programs, as well as partnership networks, thus the empowerment can be sustainable. Meanwhile, the other 2 indicators that have not been achieved maximally are including Enabling, where the BUMDES "Bareng Lestari" has not been able to create good possibilities or atmospheres that allow the community to develop optimally, because in fact, there are still many barriers between communities which make it difficult for the weak communities to develop; and Protecting, which is not optimal because there are still unachieved work programs due to the lack of participation from the community.